Re-thinking research on born globals - Coviello, Nicole (Journal of International Business Studies, 2015)
Knight and Cavusgil’s Journal of International Business Studies Decade Award-winning article offers numerous contributions to international business research. As one example, it advances cross-disciplinary conversation about entrepreneurial internationalization. A critical review of their study reveals, however, that certain findings require reinterpretation. This commentary does so, discussing the resultant implications and the question of when it is (in)appropriate to use the term “born global”. Parts of Knight and Cavusgil are then used as a foundation to identify research questions at the level of the firm. Finally, points from Cavusgil and Knight’s retrospective are used to argue that we need greater understanding of the individual(s) that are central to the firm’s internationalization behaviour. Suggestions for research are made by drawing on concepts and theory from the entrepreneurship, innovation and psychology literatures.